The small and rural academic library : leveraging resources and overcoming limitations. - Kendrick, Kaetrena Davis (Association of College and Research Libraries, 2016)
Through the use of case studies, research, and practical interviews, The Small or Rural Academic Library: Leveraging Resources and Overcoming Limitations explores how academic librarians in such environments can keep pace with, create, and improve modern library practices and services, network with colleagues, and access continuing education and professional development opportunities.